The Use of Media in Innovative Learning to Improve Students’ Achievement in Learning English - Anggia Susanti; Usman Kasim; Diana Achmad; Burhansyah Burhansyah; Chairina Nasir (Universitas Syiah Kuala, 2022)
This is a library research which aims at finding out the use of media in teaching English is implemented and aims at finding out the use of media in innovative learning to improve students’ achievement in learning English based on literature analysis. The data were collected using investigation technique of discourses from textbooks, articles, journals, papers and other relevant data sources. There are 10 sources in this study, those are: Sutirman (2013), Rahmi (2014), Mudofir (2015), Tanggoro (2015), Muktamir (2017), Nurrita (2018), Hanif (2019), Nurdyansyah (2019), Emilda (2020), and Maru'ao (2020). The researcher analyzed the data by reading deeply to get understanding of the important data from all of the sources. The researcher reviewed to look for similarities or association between one source and another source. After that, the researcher paraphrased and elaborated the statements to give valuable information. The data analysis technique included the process of data identification from relevant literature sources. The findings from the selected data were explained and summarized by where the data are located, how the data are obtained, evaluated, and incorporated into the research presentation. The result of the analysis from all the sources showed that the implementation of the use of media in teaching English to junior and senior high school students and the use of media in innovative learning can improve students’ achievement in learning English.